Transcriptome and network analyses reveal key pathways and genes involved in response to carotenoid deposition in scallop muscle - Li, Tingting; Zhang, Yihan; Liu, Shiqi; Li, Moli; Yao, Ruixing; Niu, Senyu; Yuan, Jingyao; Wang, Huizhen; Hu, Jingjie; Bao, Zhenmin; Hu, Xiaoli (Frontiers in Marine Science, 2023)
Carotenoids are essential nutrients for humans and animals, and carotenoid content has become an important trait to evaluate the nutritional value of many cultured animals. Marine animals provide humans with diverse carotenoids, and developing carotenoid-enriched varieties has been the focus of marine animal breeding. Understanding the molecular mechanism of carotenoid deposition could benefit marine animal breeding for carotenoid content improvement. In the present study, transcriptomic analysis of adductor muscle was performed between Yesso scallop (Patinopecten yessoensis) with white muscle (WM) and carotenoid-enriched orange muscle (OM). A total of 683 differentially expressed genes (DEGs) were identified, with 302 and 381 genes being up- and down-regulated in OM scallop. Gene co-expression network analysis identified four carotenoid accumulation−related modules, including three up-regulated modules and one down-regulated module. The genes in up-regulated modules mainly participate in the pathways of translation and transcription (MEgreen), immune system (MElightyellow), and lipid metabolism (MEpink), while the down-regulated module is mainly enriched with genes involved in various metabolic pathways (MEturquoise). As the causal gene responsible for muscle coloration in scallop, PyBCO-like 1 is the hub gene of MEturquoise and showed strong connectivity with NR2F1A, a transcriptional factor involved in the regulation of retinoic acid. In addition, the up-regulated DEGs, including WDR3, RPP29, TBL3, RIOK2, and NOB1 from “ribosome biogenesis”, HSP70s and HSP702Bs from “antigen processing and presentation”, and ACOX1 from “PPAR signaling pathway” were identified as hub genes, indicating the potential regulatory role of these genes and pathways in response to carotenoid accumulation. Our data contribute to a deeper understanding of the regulatory and response mechanisms of carotenoid accumulation in marine animals.